Indirect Annuloplasty to Treat Functional Mitral Regurgitation: Current Results and Future Perspectives - Patterson, Tiffany; Adams, Heath; Allen, Christopher; Rajani, Ronak; Prendergast, Bernard; Redwood, Simon (Frontiers in Cardiovascular Medicine, 2019)
The incidence of mitral regurgitation (MR) is approximately 1.7% in the developed world, and this increases to more than 10% in patients aged over 75 years. Functional (or secondary) mitral regurgitation (FMR) is defined as poor leaflet coaptation and tethering secondary to either ischemic or non-ischemic left ventricular (LV) dysfunction and dilatation. FMR is more common than degenerative (or primary) MR and is associated with significantly worse outcomes in patients with heart failure, post myocardial infarction and following coronary artery bypass graft surgery. Patients with severe degenerative MR have excellent outcomes with surgical repair, however the benefits of surgery in FMR are less clear. Although annuloplasty is associated with a lower operative mortality compared to replacement, the recurrence rate of mitral regurgitation is high in patients with FMR and neither surgical repair or replacement have been shown to reduce hospitalisation or death in FMR. Furthermore, nearly half of patients are deemed too high risk for surgery and therefore most patients are managed conservatively and there remains an unmet clinical need. Transcatheter mitral valve interventions are an emerging alternative for those at high surgical risk. This mini review focuses on indirect mitral annuloplasty: anatomical considerations, patient selection, current devices, implantation techniques and the associated clinical outcome data.